Complement C1q synergizes with PTX3 in promoting NLRP3 inflammasome over-activation and pyroptosis in rheumatoid arthritis. Issue 106 (January 2020) - Wu, Xun-yao; Li, Ke-tian; Yang, Hua-xia; Yang, Bo; Lu, Xin; Zhao, Li-dan; Fei, Yun-yun; Chen, Hua; Wang, Li; Li, Jing; Peng, Ling-yi; Zheng, Wen-jie; et al.
Abstract: Excessive inflammatory cytokines play crucial roles in the pathogenesis of rheumatoid arthritis (RA), however, the underlying mechanism remains unclear. In this study, we demonstrated that pentaxin 3 (PTX3), an essential component of innate immunity, was elevated in RA and preferentially bound to CD14 + monocytes. C1q promoted the binding and resulted in increased cell proliferation, activation and caspase-1-related late apoptotic cells (7-AAD + annexin V + ), as well as enhanced release of inflammatory cytokines including TNF-α, IL-1β and IL-6. Serum from RA patients, compared with healthy controls, induced gasdermin D (GSDMD)-dependent pyroptosis in monocytes, and this ability was associated with disease activity. Moreover, PTX3 synergized with C1q to promote pyroptosis in RA-serum pre-incubated monocytes by coordinately enhancing NLRP3 inflammasome over-activation and inducing GSDMD cleavage, cell swelling with large bubbles, caspase-1-dependent cell death and inflammatory cytokine release including IL-6. On the other hand, IL-6 promoted PTX3 plus C1q-induced pyroptosis in both normal and RA serum pre-incubated monocytes. These findings collectively implicated an important role of IL-6 in driving PTX3 plus C1q-mediated pyroptosis in RA and shed lights on a potential new treatment strategy targeting pyroptosis-mediated persistent inflammatory cytokine release. Highlights: PTX3 has been suggested as a novel marker for the diagnosis of RA, its role in the pathogenesis of RA remained inclusive. We found IL-6 activity drives PTX3 and its ligand C1q to promote NLRP3 inflammasome over-activation, GSDMD-conferred pyroptosis and inflammatory cytokine release in RA-derived monocyte in a positive feedback loop. We shed lights on a potential new treatment strategy targeting pyroptosis-mediated persistent inflammatory cytokine release.